Radon, Radium, and Uranium Concentrations in the Blood of Cigarette-Smoking Women and Lung Cancer Risk - Kadhim , Hasan Abdulhadi; Al-Alawy , Iman Tarik; Mkhaiber , Ahmed Fadhil (Iraqi Journal of Science, 2023)
Radon and its daughters are of the natural radioactive decay of the uranium series. Exposure to radon gas leads to lung cancer, so the risks are significantly higher for smokers than for non-smokers. Therefore, the risk of radon increases for both active and passive smokers. The radioactivity of alpha particles emitted by radium 226, the main source of radon 222, has become harmful because its prevalence and inhalation increase with increased smoking. In this study, a CR-39 detector was used to measure radon, radium, and uranium concentrations and then calculate risk parameters in seven cigarette-smoking females in vitro study of human blood samples, and three normal females with no actual and passive cigarette smoking. The radon concentrations in blood samples varied from 147.36±0.08 Bq/kg to 659.92±0.04 Bq/kg with an average of 316.83±150.42 Bq/kg, the radium concentration varied from 13.55±0.27 Bq/kg to 60.70±0.13 Bq/kg with an average value 29.05±13.84 Bq/kg, and uranium concentration varies from 11.89±0.29 ppm to 53.23±0.14 ppm with an average value 25.47±12.13 ppm. The annual effective dose ranged from 4.42±0.48 to 12.57±0.28 mSv/y with average value of 8.35±3.10 mSv/y. The annual risk cases of lung cancer varied from 79.50±.0.11 to 226.26±0.07 with an average value of 150.22±55.78 per million people. The results deal with the radioactive effect of female cigarette smokers as a risk factor for lung cancer. Most of the results exceed the permissible international limits. Hence, human health and their life are at risk of radioactivity resulting from cigarette smoking that is concentrated in the blood of female smokers examined in this work.